Licensing Management Challenges: The Case of Migrants’ Application of Food Establishment and Industrials/Trade Business in Alor Setar City Council (Journal of Governance and Development (JGD), 2018)
This study aims to examine the challenges in dealing with licensing issues involving the business of food and business establishments/trade conducted by foreigners in the case of Alor Setar City Council. The inï¬‚ux of foreigners who run non-licensed food stalls and restaurants business is increasingly widespread â€” however, no appropriate action imposed on them. The study employed qualitative design with an interview session with two license department ofï¬cers from Alor Setar City Council. The ï¬ndings demonstrate that Alor Setar City Council facing difï¬culties to implement the laws towards illegal business conducted by foreigners as most of them closed their premises during the raid and inspection. Some foreigners do business by selling food and other businesses such as grocery stores by hiring shop lots or land from local people. They are also found to have rented shops and land to be used as a business site space such as a restaurant or business of goods from their home country. Based on the existing provisions of the bylaw, there is no provision stating that business by a foreigner is not allowed. The use of the existing legislation of the bylaws has to be reviewed from the aspect of licensing for enforcement on unlicensed foreignersâ€™ premises.